2021
DOI: 10.7759/cureus.17139
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Three-Dimensionally Printed Ultrasound-Guided Peripheral Intravenous Catheter Phantom

Abstract: IntroductionUltrasound-guided peripheral intravenous catheter (US-PIVC) placement is an effective technique to establish PIV access when the traditional approach fails. Many training programs utilize commercial or homemade phantoms for procedural training. However, commercial products tend to be expensive and lack realism, while homemade blocks tend to be single-use and degrade easily. Thanks to the increasing availability of three-dimensional (3D) printers in academic settings, we sought to design and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…Successful testing in large deep central vessels and shallow superficial peripheral veins demonstrates the adaptability of the phantom fabrication methodology and the translatability of AI-GUIDE to diverse applications. 3D-printing of vascular phantoms has emerged recently as an active area of investigation [7][8][9][10]. Many investigations focus on utilization of custom phantoms to optimize clinical procedural planning or for use in clinician education with excellent effect.…”
Section: Discussionmentioning
confidence: 99%
“…Successful testing in large deep central vessels and shallow superficial peripheral veins demonstrates the adaptability of the phantom fabrication methodology and the translatability of AI-GUIDE to diverse applications. 3D-printing of vascular phantoms has emerged recently as an active area of investigation [7][8][9][10]. Many investigations focus on utilization of custom phantoms to optimize clinical procedural planning or for use in clinician education with excellent effect.…”
Section: Discussionmentioning
confidence: 99%
“…Erfahrungen der Simulationsausbildung von Piloten und Chirurgen zeigen jedoch, dass diese den einfachen Phantomen in Abhängigkeit vom Ausbildungsziel nicht zwangsläufig überlegen sein müssen [15,16]. [17,18,19]. Vorteilhaft ist die Nutzung des normalen Ultraschallgerätes, sodass die erforderlichen Techniken zur Bildeinstellung und Bildoptimierung ("Knöpfologie") realistisch geübt werden können.…”
Section: Historische Entwicklung Der Simulationunclassified
“…Mit ihnen können gezielt einzelne Aspekte trainiert werden ("Part-task-Konzept"). So werden sie vor allem für das Training interventioneller Techniken wie beispielsweise das Legen von Gefäßzugängen oder Organpunktionen genutzt [17,18,19]. Vorteilhaft ist die Nutzung des normalen Ultraschallgerätes, sodass die erforderlichen Techniken zur Bildeinstellung und Bildoptimierung ("Knöpfologie") realistisch geübt werden können.…”
Section: Historische Entwicklung Der Simulationunclassified
“…Similarly, using easy-to-purchase 3D printing components, Lord et al produced a durable pericardiocentesis chest model for less than USD 110 (material costs) [ 144 ]. As for vascular access, Tan et al compared a 3D-printed ultrasound-guided peripheral intravenous catheter (US-PIVC) phantom and five times more costly (USD 120 vs. USD 549) commercial model in terms of time to placing a US-PIVC by 21 emergency medicine physicians and found that there was no significant difference in mean time PIVC placement and realism between the two groups [ 145 ]. In another study, Engelbrecht et al found the 3D-printed trainer to be a practical tool for practicing intraosseous techniques among rural medicine residents, rural emergency medicine physicians, and nurses [ 146 ].…”
Section: Discipline Specific Applicationsmentioning
confidence: 99%